Mandibular temporary immobilization after closed reduction of TMJ luxation with use of surgical mask: technical note - Shinohara, Elio Hitoshi; Yokoyama, Plínio Jun Iti; Horikawa, Fernando Kendi; Lemos-Junior, Celso Augusto; Snidei, Iron Ricardo Machado (ARCHIVES OF HEALTH INVESTIGATION, 2018)
The acute dislocation of the temporomandibular joint (TMJ) is usually reduced using the Hippocratic method/Nelaton maneuver. It is recommended the temporary immobilization of TMJ for pain relief and remission of the inflammatory process that affects the ligaments and articular capsule. This containment is traditionally made with cotton bands but difficult to find if this type of material in a dental office. We present a simple method of mandibular immobilization using disposable surgical mask. We believe it’s as effective as the traditional bandage, easily and quickly applied, cheaper and made with material that is readily available in dental offices. We are using this device for more than 15 years with excellent results and we recommend the use. Descriptors: Temporomandibular Joint; Fracture Fixation; Immobilization.